Determinants level of profitability for banking companies listed in KLSE / Sharizaida Othman - Othman, Sharizaida (2010)
This project paper examines the level of profitability of banking sectors in relation to the bank characteristics, financial performance and macroeconomic indicators. Generally, this study is conducted on banking companies listed in Main Market Kuala Lumpur Stock Exchange. The sample period is from the year 2005 to 2009. The objectives are to to identify the strength and direction of the relationship of the determinants of level of profit in banking sector and to identify which of the independent variables that most influencing the level of profit in banking sector. A sample of twelve companies has been tested and analyzed to represent a population of 30 companies in the sector. The method used is Simple Linear Regression and Multiple Linear Regression Analysis to identify association between profit, bank characteristics, financial performance and macroeconomic indicators. As for the overall result, it shows that all the independent variables affect the profit (dependent variable) and also positively related to the profit.